Design and Validation of a Tool to Collect Student-Athletes' Perception of Their Satisfaction - Josè M. Palao; Bridget Jost; Janel Katzer; Megan Parietti (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2023)
The purpose of this study was to design and validate a tool to collect the student-athletes' perception of their satisfaction. The instrument collects information regarding student-athlete characteristics, self-perception, perception of training, perception of team/teammates, perception of the program organization, and perception of the support received. The design and validation, of the questionnaire were done in two phases: a) design and development of the instrument, and b) content validation by experts. The results show that the tool is suitable for obtaining information about student-athletes' perception of their satisfaction. The implementation of the tool involves two phases: a) student-athletes completion of a survey and b) student-athletes and moderator carry out a group discussion regarding the causes behind their answers, things to maintain, and things that could change or improve. The tool developed and validated could contribute to increase the information of student-athletes about their experience and generate communication channels.